2019
DOI: 10.1111/hdi.12719
|View full text |Cite
|
Sign up to set email alerts
|

Experience with antiviral agents for treatment of hepatitis C virus infection in hemodialysis patients on the kidney wait list

Abstract: Introduction Hepatitis C virus (HCV) infection is associated with increased mortality and morbidity in kidney transplant patients. The ability to establish a sustained viral response before renal transplant is important for these patients. Direct‐acting antiviral agents can increase the sustained viral response in most patients with HCV infection. In this case series, we aimed to determine the efficacy and safety of a combined therapy of ombitasvir, paritaprevir, ritonavir, and dasabuvir with or without ribavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
1
4
0
1
Order By: Relevance
“…In the literature, the most common side effects of PrOD were fatigue and pruritus (9,10,11,12). In our study the most common side effect was pruritus, which was observed in 3 patients.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…In the literature, the most common side effects of PrOD were fatigue and pruritus (9,10,11,12). In our study the most common side effect was pruritus, which was observed in 3 patients.…”
Section: Discussionsupporting
confidence: 46%
“…After RUBY-I trial was published, SVR rate >95% was observed and eradication of HCV in ESRD patients became much more possible (8). The real-life experiences published after RUBY-I showed that SVR rates were equal to or greater than those reported in RUBY-I trial (9,10,11,12,13).…”
Section: Discussionmentioning
confidence: 99%
“…Torun et al reported that hemoglobin level, white cell blood count, and thrombocyte count were similar to pretreatment levels and SVR12. 16 During treatment, total bilirubin levels were elevated in f ive patients during the f irst two weeks and decreased below normal limits in the first month.…”
Section: Discussionmentioning
confidence: 94%
“…Patients were divided into two groups according to the genotype; 3/10 were genotype 1a, 7/10 genotype 1b, and the reported SVR 12 rate was 100%. 16 The study published by Etik et al evaluated 30 CHC patients(18 patients with ESRD and 12 kidney transplant recipients). They reported that SVR 12 was 94% of patients in the ESRD group and 92% in the kidney transplant group.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of death and disease have been estimated worldwide, and a larger increase has been associated with infection with the HCV. It has been found that about7 million people normally experience fatal complications from HCV-associatedsigns clinically due to hepatocellular carcinoma (HCC) and cirrhosis each year 16 . The World Health Organization has also identified a cure for HCV infection by treatment with antivirals; though, maximum people who are infecteduninformed of the infection because of the disease asymptomatic nature.…”
Section: Discussionmentioning
confidence: 99%